2019
DOI: 10.21608/adjalexu.2019.57614
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage Evaluation of Bulk-Fill Composite in Class Ii Restorations of Primary Molars

Abstract: INTRODUCTION:Bulk-fill composites are promising restorative materials which may minimize placement time yet provide successful, durable esthetic restoration. OBJECTIVES: The purpose of this in vitro study was to evaluate marginal microleakage of nano-hybrid bulk-fill composite, and compare it to incrementally placed conventional nano-hybrid composite when used to restore proximal cavities in primary molars. MATERIALS AND METHODS:The sample consisted of 44 freshly extracted sound primary molars. Standardized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…25 Another hypothesis is that the materials share similar properties and consistency. 26 Nanohybrid resin composites (Tetric N Ceram, Mosaic and Harmonize) showed the least microleakage. These results were consistent with those of Shah et al, who compared nanohybrid resin composites to microfilled resin composites.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Another hypothesis is that the materials share similar properties and consistency. 26 Nanohybrid resin composites (Tetric N Ceram, Mosaic and Harmonize) showed the least microleakage. These results were consistent with those of Shah et al, who compared nanohybrid resin composites to microfilled resin composites.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, future research could help us understand more about the clinical performance, durability, and efficacy of resin composite restorations. 26 …”
Section: Discussionmentioning
confidence: 99%
“…20 About 2% MB dye was selected for this study because of its low molecular size which allows for the detection of minutest leakage where even bacteria cannot penetrate and is a more sensitive indicator of leakage. 19,20,[22][23][24] The dye-penetration studies are popularly employed due to their low cost and simplicity of technique and do not necessitate sophisticated materials, but they give questionable results. In the present study, the fluidfiltration and dye extraction techniques allowed the scaling of four perforation repair materials and presented corresponding results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that BF composite has lower polymerization shrinkage and gap formation than conventional composites [26,27]. Other studies, however, showed comparable shrinkage for both material types [28,29]. Studies focusing on photoinitiator systems in both BF and conventional composites are very scarce.…”
Section: Discussionmentioning
confidence: 99%